KONSEP KELUARGA SAKINAH DAN IMPLIKASINYA TERHADAP PENDIDIKAN ANAK - St. Aisyah Abbas; Nur Rahma Asnawi (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2019)
This paper discusses the concept of a happy family and its implications for children's education responsibilities. The main problem in this paper is how the concept of a happy family and its implications for the responsibility of children's education. With a descriptive approach, namely the study of library research by examining a variety of qualitative references it can be concluded that the concept of a happy family in the view of Islam is a family bond in which there are various elements that describe a conducive, secure, prosperous and peaceful atmosphere based on the guidance of the Koran and hadith. Meanwhile the concept of education that takes place in the household should always maintain values ​​that are in accordance with religious teachings and create religious nuances in the household by applying several methods of Islamic education including exemplary, habituation and training, giving advice and warnings and punishments. The family influence is happy with the responsibility of children's education, lies in the establishment of a family institution that is peaceful, sentimental, and full of affection will provide positive implications for the educational process in order to direct the potential and talents of children towards achieving maturity and in turn children can grow and develop naturally so that it becomes a generation of Muslims who are Quranic, militant and istiqomah